Análisis de la percepción social del riesgo por covid-19 en la Parroquia de Tufiño. - Muñoz Arciniegas, Yesenia Aracely (2021)
The objective of this scientific article is to evaluate the social perception of risk by covid-19 in older adults in the town of Tufiño parich. In which the following research question is generated: ¿What methodology for the evaluation of risk perception is appropriate to apply in older adults? In order to answer the question it is necessary to collect information regarding the research topic, in the same way two different surveys should be applied to the older adults of the town of Tufiño parich base don the evaluation methodologies of risk perception taken into account which are EPRO and Delphi. The results obtained show that Delphi is the appropriate methodology to determine the social perception of risk of adults with greater ease and unterstanding because it allows the collection of a greater amount of information through the freedom of expresión of emotions, feelings, ideas, and others of the people surveyed, unlike EPPRO, which is base don generating questions base don previously determined variables to generate a number value that allows the interpretation of the perception of risk without taking into account the social part.